2020
DOI: 10.3390/pr8050631
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Processes Management for a Sustainable Society: Global Research Analysis

Abstract: Few decades ago, the development of the industrial sector was disconnected from society’s protection. Negative effects awareness emerges from the current industrial processes through the Sustainable Development Goals (SDGs), considering the causal implications to build up a more sustainable society. The aim of this study is to analyze the state of the art in industrial processes management to obtain positive and sustainable effects on society. Thus, a bibliometric analysis of 1911 articles was set up during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 144 publications
0
29
0
Order By: Relevance
“…All analyses were performed using the bibliometric method [87][88][89]. Through this method, which has been used in more than 3200 investigations, the most relevant aspects of the subject under study were identified and described.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed using the bibliometric method [87][88][89]. Through this method, which has been used in more than 3200 investigations, the most relevant aspects of the subject under study were identified and described.…”
Section: Methodsmentioning
confidence: 99%
“…These prolific authors produced a high number of articles and achieved high scientific impact in research. The h-index is an important metric used to evaluate the cumulative impact of a researcher’s publication output and performance by comparing the publications to citations [ 29 , 30 ].…”
Section: Application Of Microbial Community In Biodegradation Of Hmentioning
confidence: 99%
“…This paper utilized a comparative bibliometric study between two different focus of studies by quantifying the articles published over the years followed by extracting the information and then presented using network analysis. However, several other methods such as qualitative measurements using questionnaires on the opinions of people with various backgrounds and seeking experts for constructive discussions could be combined with the traditional bibliometric approach (hybrid model) [ 30 , 31 ]. Alternatively, a topology structure and model mapping could also be used to determine the extent of advancement over different fields or disciplines and increase the robustness of the bibliometric analysis [ 13 , 32 ].…”
Section: Application Of Microbial Community In Biodegradation Of Hmentioning
confidence: 99%
“…For this reason, in the context of scarcity and fluctuation in the costs of raw materials, the CE contributes to the security of supply and to the re-industrialization of the national territory. Therefore, it manages to convert waste into raw materials, as a paradigm of a future system [51,52].…”
Section: Literature Reviewmentioning
confidence: 99%